The analysis of implementation in public relations to establishment the effort of the brand image coworking (a study at coworking space ETOS of Yogyakarta) - Musdalifa, Musdalifa; Fajri, Choirul (COMMICAST, 2021)
ETOS co working space, one of the workspaces located in Yogyakarta that carries a simple concept, but is still in demand by the public. Manyhave emerged co-working spaces with attractive concepts and are in demand by many people. ETOS still carries the concept of "real co-working space" and competes with its competitors, and in less than a year ETOS has already received regular clients and customers every day. With the title "The Analysis of the Implementation Public Relations to Develop The Effort of The Brand Image Co working space" with the formulation of the problem of how to use the role of public relations in an effort to increase the brand image of the ETOS co working space in Yogyakarta with the aim of research, namely to determine the use of the role of public relations in an effort to improve brand image co working space ETOS. This research uses descriptive qualitative research methods. Data collection techniques are carried out using observation, interviews, and documentation. This research process focuses on utilizing the role of public relations in an effort to increase the brand image of the co-working space at ETOS. By using several data analysis techniques such as data reduction, display data, and conclusion drawing / verification. For data validation, this study used triangulation techniques. Based on the research results obtained in the field, it is concluded that in an effort to improve the brand image of the ETOS co working space , ETOS Public Relations takes advantage of the role of public relations , namely, expert prescribe, communication facilitator, problem solving facilitator, and communication technician. ETOS PR also implements management public relations in this case planning, implementation, and evaluation.